Governance of densification and climate change adaptation: How can conflicting demands for housing and greening in cities be reconciled?. (May 2023) - Erlwein, Sabrina; Meister, Juliane; Wamsler, Christine; Pauleit, Stephan
Abstract: Urban green spaces are important for climate change adaptation, in particular to reduce the negative impacts of heat waves on human well-being. However, in growing cities urban green spaces are under pressure due to increasing housing demand and densification. Municipalities face the challenge of addressing both the housing shortage and the need for climate change adaptation on limited space. This study assessed the barriers that hinder successful integration in urban policymaking. More specifically, it analyses structural conditions impeding or promoting climate resilient urban development in growing, densifying areas. Based on interviews with urban and green space planning officers and policy analyses, we investigate current discourses and the interrelations between actors, power, resources and regulations. Our results show that improved cooperation between individual administrative departments, as well as administration and politics is decisive for better integration of green spaces in urban planning, negotiations with investors and sustained citizen involvement. Certain departmental structures and working routines can help to promote such cooperation. We show that it is not the availability of resources alone that is key for integration, as commonly suggested. Instead, transparent communication, the co-development of rules and resolutions with the public, and strategic external resource management are needed for solving conflicting demands for densification and greening in cities. We conclude with recommendations for research, policy and practice. Highlights: Lack of financial and human resources alone does not explain low consideration of urban green. Instead, interrelations between actor coalitions, regulations, resource distribution and discoursehave to be considered. Integration of greening requires improved cooperation between municipal actors. Integrative departmental structures and working routines help to promote cooperation of municipal actors. Transparent communication and co-development of rules with the public is recommended.